ANTIMICROBIAL ACTIVITY OF ANTHOCEPLALUS CADAMBA AND SCIRPUS KYSOOR ROXB. AGAINST FOOD PATHOGENS - Datar, Hemangi; Datar, Ajit (International Journal of Current Pharmaceutical Research, 2016)
Objective: Aim of the present study was to evaluate the antimicrobial activity of ripened and unripened fruits of Anthocephalus cadamba and Scirpus kysoor Roxb. tuber against food pathogens. Methods: Different solvent extracts of Anthocephalus cadamba fruits and Scirpus kysoor Roxb. tubers were screened for its antimicrobial activity against Gram negative and Gram positive bacterial cultures by agar well diffusion method as well as by minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). MIC was carried out by broth microdilution method. Results: All the plant materials exhibit antimicrobial activity. Among all plant materials, macerated ethyl acetate extract of Scirpus kysoor Roxb. tuber showed lowest MIC against Bacillus Cereus 0.312 mg/ml. In the case of ripened Anthocephalus cadamba fruits, macerated ethanol extract was found to be more potent whereas in the case of unripened Anthocephalus cadamba fruit macerated ethyl acetate extract was found to be more active on the basis of MIC. Conclusion: This study revealed that all the plant materials possess significant antimicrobial activity against food pathogens hence may be used as a source of safe herbal antimicrobial agent.